Survey on a Cohort of Subjects Aged From 6 Months to 18 Years and Born to Mothers Managed for Thyroid Hypo-Function in Pregnancy. Experience in a Single Non-Academic Centre in Liguria, Italy - Giusti, Massimo (British Journal of Healthcare and Medical Research, 2023)
Background: The adequate management of thyroid dysfunction in pregnancy reduces pre-partum adverse events and improves the life of the new-born. Aim: Women managed for thyroid hypo-function during pregnancy were retrospectively identified and a survey was performed on their offspring aged from 6 months to 18 years. Methods: We selected 131 pregnancies for survey. From January to August 2022, the mothers were sent a questionnaire containing questions on the neonatal and post-natal period and questions on their children’s current auxological, scholastic and pathological status and lifestyle. Eighty-two questionnaires were returned. The mothers’ replies were compared with their f-T4 and TSH levels recorded during pregnancy. Reference f-T4 and TSH values were extrapolated from 76 pregnancies managed according to current guidelines. Results: f-T4 values below the 2.5th percentile were found in less than 3% of cases, while f-T4 values above the 97.5th percentile were found in less than 4%. TSH proved more variable. Replies regarding the time of the new-born’s first postural changes were significantly inversely correlated with f-T4 concentrations in each trimester of pregnancy and positively correlated with the TSH levels observed in the 1st trimester. Conclusions: This single-centre, cross-sectional, study offers further indications for the management of thyroid hypofunction in pregnancy and suggests that the control of maternal f-T4 and TSH levels during pregnancy has improved in our district. Data from survey indicate that f-T4 influences early motor activity in new-borns more than TSH does. However, the small sample size, the wide age range of the children and the long time-lag between delivery and survey administration could impair our results.